Alcohol and cancer: A position statement from Cancer Council Australia - Winstanley, M.; Pratt, Steve; Chapman, K.; Griffin, H.; Croager, E.; Olver, I.; Sinclair, C.; Slevin, Terry (2011)
The Cancer Council Australia (CCA) Alcohol Working Group has prepared a position statement on alcohol use and cancer. The statement has been reviewed by external experts and endorsed by the CCA Board. Alcohol use is a cause of cancer. Any level of alcohol consumption increases the risk of developing an alcohol-related cancer; the level of risk increases in line with the level of consumption. It is estimated that 5070 cases of cancer (or 5% of all cancers) are attributable to long-term chronic use of alcohol each year in Australia. Together, smoking and alcohol have a synergistic effect on cancer risk, meaning the combined effects of use are significantly greater than the sum of individual risks. Alcohol use may contribute to weight (fat) gain, and greater body fatness is a convincing cause of cancers of the oesophagus, pancreas, bowel, endometrium, kidney and breast (in postmenopausal women). The existing evidence does not justify the promotion of alcohol use to prevent coronary heart disease, as the previously reported role of alcohol in reducing heart disease risk in light-to-moderate drinkers appears to have been overestimated. CCA recommends that to reduce their risk of cancer, people limit their consumption of alcohol, or better still avoid alcohol altogether. For individuals who choose to drink alcohol, CCA recommends that they drink only within the National Health and Medical Research Council guidelines for alcohol consumption.